The Impact of Financial Literacy Levels on Investment Decisions for Children's Education Among Rural Housewives - Latifah, Umi; Nur Amiin, Siti; Nuraini, Latifah (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2025)
This study investigates the level of financial literacy of rural housewives and its impact on children's education investment decisions. A quantitative descriptive method was employed, utilizing Moderated Regression Analysis (MRA). The sampling technique used was non-probability sampling, specially a convenience sampling method, which involved distributing questionnaires. The results of this research indicate that housewives have a relatively high financial literacy level, with an average score of 56.79. Most housewives in the villages of Sambilawang and Kadilangu hold a high school and bachelor's degree. This level of financial literacy has a significant impact on children's education investment (11 %), while the rest are influenced by other variables but has a relatively low investment in children's education funds at 0.66. because of the income earned from the Rp. 1,000,000 to < 2,500,000 per month and the average job of these housewives. are the majority of the officers or employees. The Research subjects consisted of 53 housewives in the Sambilawang, Kadilangu village, Trangkil sub-district, Pati district. This study recommends a policy to increase financial literacy among rural housewives and optimize investment in children's education to create more sustainable economic conditions in rural communities